Main Organiser - Katsamba, Panayiota (My University, 2026)
Hosting of approximately 20 delegates representing the Industrial Mathematics National Networks of Europe , for the Annual Council of the EU-MATHS-IN Network on the 3rd of December 2025. Hosting of the satellite event titled ''Industrial Mathematics Driving Sustainable Economy Innovations'' on the 4th of December 2025. https://www.cut.ac.cy/news/article/?contentId=621820